Genetic polymorphisms of TGF-β, PAI-1, and COL1A-1, and determination of bone mineral density in caucasian females - Hubáček, Jaroslav; Weichetová, Markéta; Bohuslavová, Romana; Škodová, Zdenka; Štěpán, Jan; Adámková, Věra (Endocrine regulations, 2006)
Objective: The aim of this study was to examine whether the variants in genes for transforming growth factor β1 (TGF-β1; Leu10>Pro and Arg25>Pro), plasminogen activator inhibitor 1 (PAI-1; 4G>5G variant) and collagen -1 (COL1A-1; Sp1 variant) may be useful in identifying individuals with increased susceptibility to early postmenopausal bone loss within the population of Czech women. Methods: Polymorphisms were genotyped (by PCR and restriction analysis) in 1400 females representatively selected from the Czech population as well as in 218 postmenopausal osteoporotic women 40-70 years of age (mean age 58,7 years) and a 151 control group of postmenopausal females in the same age range (mean age 59,1 years) with normal BMD. Results: We have not found any statistically significant differences in the frequency of the individual genotypes or alleles of analyzed variants between the groups of osteoporotic patients (OP), population group (PG) and control group (CG). The frequencies of the individual genotypes in the analyzed groups were as follows - 1) TGF-β1 gene: Leu10Leu10 OP – 30.2%, PG – 35.6%, CG 35.1%; Leu10Pro10 OP – 52.1%, PG – 47.1%, CG 50.0%; Pro10Pro10 OP – 17.7%, PG – 17.3%, CG 14.9%; 2) TGF-β1 gene Arg25 homozygotes OP – 83.8%, PG – 86.1%, CG – 89.3%, Pro25 carriers OP – 16.2%, PG – 13.9%, CG – 10.7%, 3) PAI-1 gene: 4G4G OP – 34.9%, PG – 31.8, CG – 28.5%, 5G4G OP – 43.6%, PG – 46.7%, CG – 50.3%, 5G5G OP – 21.5%, PG – 21.5%, CG – 21.2%, and 4) COL1A-1 (“SS” homozygotes, OP – 63.0%, PG – 63.7%, CG – 64.9%, “s” carriers OP – 37.0%, PG – 36.3%, CG – 35.1%). Conclusions: Variants in genes for TGF-β1 (Leu10>Pro and Arg25>Pro), PAI-1 (4G>5G) and COL1A-1 (Sp1 variant) are not associated with low BMD in postmenopausal Czech Caucasian females.
Keywords: referenční hodnoty; Humans; lidé středního věku; kolagen typu I; běloši; polymorfismus genetický; Osteoporosis, Postmenopausal; Female; Aged; dospělí; Collagen Type I; White People; senioři; lidé; Polymorphism, Genetic; Adult; ženské pohlaví; postmenopauzální osteoporóza; Middle Aged; Genetic Predisposition to Disease; genetická predispozice k nemoci; Bone Density; transformující růstový faktor beta; Czech Republic; kostní denzita; Transforming Growth Factor beta; Reference Values; inhibitor aktivátoru plazminogenu 1; Česká republika; Plasminogen Activator Inhibitor 1